FACTORS AFFECTING UNDERSTANDING AND USING OF STANDAR AKUNTANSI KEUANGAN TANPA AKUNTABILITAS PUBLIK ON MSMEs (SURVEY CONDUCTED OF ENTREPENEURS GETUK GORENG IN BANYUMAS REGENCY) - Thiya Septriana; Puji Lestari; Dona Primasari (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2020)
This research aims to determine the effect of variable Level Education, Socialization of SAK ETAP, Business Scale, and Business Age on Understanding and Use of SAK ETAP at Getuk Goreng entrepreneurs in Banyumas Regency. The sample in this study amounted to 54 entrepreneurs of Getuk Goreng in Banyumas Regency by using the census method, which is to take a sample of the population. The Theories used in this research are Human Capital Theory and Unified Theory of Acceptance and Use of Technology (UTAUT). The data collection in this research was taken by distributing questionnaires, which the process by visiting directly the place of Getuk Goreng business and submitting the questionnaire that was compiled. The results obtained from the field will be analyzed using the Validity & Reliability Test, Classic Assumption Test, Multiple Linear Regression Test and this test is processed with SPSS application. The results of research that have been obtained show that the variable Socialization of SAK ETAP and Business Scale have a positive effect on the understanding and use of SAK ETAP while, the other variables are Level Education and Business Age do not affect the understanding and use of SAK ETAP.